2001
DOI: 10.1161/hy09t1.094504
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic and Metabolic Profile in Offspring of Malignant Hypertensive Parents

Abstract: Abstract-Malignant hypertension is a serious form of arterial hypertension in which the physiopathological mechanisms include increased activity of the sympathetic nervous system, renin angiotensin system, and endothelium dysfunction. Family history of hypertension is an important predictive factor for hypertension and is associated with metabolic and hemodynamic abnormalities. Studies of these abnormalities in malignant hypertensive offspring have not yet been published. Therefore, we studied 42 offspring of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
2
5

Year Published

2003
2003
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 27 publications
4
42
2
5
Order By: Relevance
“…Because of the small sample size, the higher low-density lipoprotein-cholesterol levels observed in FH þ þ group, as well as observed in the FH þ group (B18 mg 100 ml À1 ), cannot be dismissed because of the absence of statistical significance, and may have important clinical relevance. Higher low-density lipoprotein-cholesterol levels among normotensive offsprings of hypertensive parents compared with normotensive with normotensive parents have been shown by some investigators, 7,19,24,25,28 although negative finds exist. 18,26 Abnormalities in lipids, glucose and insulin metabolism have been found to be part of a complex of cardiovascular risk factors commonly found in hypertensive subjects.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 91%
See 4 more Smart Citations
“…Because of the small sample size, the higher low-density lipoprotein-cholesterol levels observed in FH þ þ group, as well as observed in the FH þ group (B18 mg 100 ml À1 ), cannot be dismissed because of the absence of statistical significance, and may have important clinical relevance. Higher low-density lipoprotein-cholesterol levels among normotensive offsprings of hypertensive parents compared with normotensive with normotensive parents have been shown by some investigators, 7,19,24,25,28 although negative finds exist. 18,26 Abnormalities in lipids, glucose and insulin metabolism have been found to be part of a complex of cardiovascular risk factors commonly found in hypertensive subjects.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 91%
“…The existence of early abnormalities of glucose and insulin metabolism among offsprings of hypertensive parents has been confirmed by some investigators, 7,19,[24][25][26] although not by all. 15,27 Previous studies have shown elevated fasting insulin and insulin-to- Early abnormalities in family hypertension EG Ciolac et al glucose levels, as well as reduced sensitivity of insulin-mediated cellular glucose disposal, in normotensive offspring of hypertensive parents; however, data have not been analysed separately by neither gender nor parental burden.…”
Section: Lipids Glucose and Insulinmentioning
confidence: 92%
See 3 more Smart Citations